2011
DOI: 10.1121/1.3586789
|View full text |Cite
|
Sign up to set email alerts
|

Failure of the Ingard–Myers boundary condition for a lined duct: An experimental investigation

Abstract: This paper deals with experimental investigation of the lined wall boundary condition in flow duct applications such as aircraft engine systems or automobile mufflers. A first experiment, based on a microphone array located in the liner test section, is carried out in order to extract the axial wavenumbers with the help of an "high-accurate" singular value decomposition Prony-like algorithm. The experimental axial wavenumbers are then used to provide the lined wall impedance for both downstream and upstream ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
108
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 17 publications
4
108
0
Order By: Relevance
“…Thirdly, and perhaps most likely, this disagreement at lower frequencies is consistent with the type of failure of the Myers boundary condition discussed in Ref. [24], where the model impedance values were found to be dependent on the direction of propagation. Therefore, waves reflected back upstream see a different impedance.…”
Section: Differences Between the Experimental And Numerical Valuessupporting
confidence: 84%
See 1 more Smart Citation
“…Thirdly, and perhaps most likely, this disagreement at lower frequencies is consistent with the type of failure of the Myers boundary condition discussed in Ref. [24], where the model impedance values were found to be dependent on the direction of propagation. Therefore, waves reflected back upstream see a different impedance.…”
Section: Differences Between the Experimental And Numerical Valuessupporting
confidence: 84%
“…It has also been shown that the Myers model fails to result in a single impedance value for wave propagation downstream and upstream in a lined duct when the acoustic boundary layer is not much smaller that the mean flow boundary layer thickness, i.e. at low frequencies [24]. This finding does not negate the use of the model altogether but rather it limits its applicability.…”
Section: A Wem-based Methodology For Computing the Propagation In A Lmentioning
confidence: 99%
“…11 In their paper, Renou and Auregan used Prony's method 12 to educe the impedance of a conventional liner using the Ingard-Myers boundary condition under the assumptions of uniform flow. They educed different impedances for an upstream and downstream source, although the incident sound pressure level and the mean flow Mach number were held constant for both sources.…”
Section: Introductionmentioning
confidence: 99%
“…They educed different impedances for an upstream and downstream source, although the incident sound pressure level and the mean flow Mach number were held constant for both sources. Because the liner impedance should not be dependent on whether the source is upstream or downstream, 11 it was concluded that "the Ingard-Myers boundary condition fails to predict with accuracy the acoustic behavior in a lined duct with flow." They presented results for a conventional liner achieved at a single flow speed to support this conclusion.…”
Section: Introductionmentioning
confidence: 99%
“…Myers' condition is easily implemented due to its simplicity and the minimum of information needed of the boundary layer geometry etc. However, the condition has been proven to fail to describe the influence of the flow above the surface, in for example 15 .…”
Section: A Myers' Boundary Conditionmentioning
confidence: 99%